THEMATIC PROGRESSION ON STUDENTS’ RECOUNT TEXTS - Safitri, Irfina; Bahri, Seful (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2017)
This paper is based on a study aimed to find out the types of thematic progression patterns the students mostly employ in their recount texts and to examine the coherence of fourth semester students’ recount texts viewed from their thematic progression of the English Department, Universitas Negeri Semarang in the Academic Year of 2015/2016 who took Genre-Based Writing (GBW) class in Rombel 1. This study was a written discourse analysis which was used to figure out the realization of meanings. The findings showed that all of the students employed more than one pattern in their recount texts. They tended to use combination between reiteration (constant), zig-zag (linear), and multiple theme patterns. However, reiteration was the most dominant one. The second dominant pattern was zig-zag pattern. The third pattern found in the students’ recount texts was multiple theme. The analysis also showed that the number of clauses and the thematic progression patterns produced by the students are not equivalent. It means that there are many clauses which are not related to one another. The students often introduced some new themes at the beginning of the clause without any relation with other clauses and they break the well signposted progression of the text. It can be concluded that most of the recount texts produced by the students are not coherent.